Potential of Cat’s Whisker (Orthosiphon stamineus B) As Antidiabetic in Traditional Medicine of The Dayak Tribe in West Kalimantan : A Literature Review - Hartono Putra, Galih Abisatya; Andayani, Sari; Qisthi, Dianelita Asyifa; Aurelion, Candra; Mochammad, Taufiq; Zakiah, Mistika; Assegaf, Syarifah Nurul Yanti Rizki Syahab (Faculty of Medicine, Hasanuddin University., 2024)
Introduction: Diabetes mellitus or better known as diabetes is a disease characterized by the body's inability to produce insulin or the inability to use insulin (insulin resistance). The high prevalence of diabetes sufferers in Indonesia requires attention and treatment, especially through medication. One of Indonesia's advantages compared to other countries is the biodiversity and cultural diversity sector in Indonesia, namely medicinal plants. The cat's whisker plant (Orthosiphon stamineus B) can be an alternative treatment for treating complications of diabetes mellitus. Cat's whisker leaves contain orthosiphon glucose, saponins, essential oils, flavonoids, polyphenols, potassium salts and myoinositol, several substances contained in this plant have the potential to lower blood sugar levels. Methods: This writing is a literature review by collecting literature from English and Indonesian language articles from 2014-2024, most of which are research articles. Results: The search using the keywords, resulting in a final total of 5 articles to be included in the literature review. Conclusion: This research reveals that cat's whiskers (Orthosiphon stamineus B) show potential as an effective antidiabetic agent. Treatment with Orthosiphon stamineus B extract significantly reduced blood glucose levels, increased insulin secretion, and increased ghrelin and GLP-1 levels, all of which contribute to glucose regulation